Community Empowerment in the Context of Sustainable Tourism Development in Surodadi Village - Syahrul Akbar; Evi Noviyanti; Uti Lies Siti Khadijah; Reiza D Deinaputra (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2021)
The purpose of this study was to identify factual and potential conditions, as well as to analyze community empowerment in the tourism sector in Surodadi Village. This research used the descriptive qualitative research method. Data were collected through field observations, literature study, and documentation. The data were then analyzed using an interactive data analysis model, including data condensation, data presentation, and drawing conclusions. Furthermore, the factual conditions, tourism potential, and community empowerment in Surodadi Village were analyzed using five dimensions of the community-based tourism approach. The results showed that there are three pillars in the development of tourism in Surodadi Village, namely the economic, environmental, and social pillars. This study also recommends four stages in the development of community-based tourism in Surodadi Village, namely by assessing the needs and readiness of the community for tourism, training and preparing the community in the field of tourism, identifying and determining local leadership, and preparing and developing community organizations.